Clinicopathological correlations of nestin expression in surgically resectable pancreatic cancer including an analysis of perineural invasion - Lenz, Jiri; Karasek, Petr; Jarkovsky, Jiri; Muckova, Katarina; Dite, Petr; Kala, Zdenek; Veselska, Renata; Hermanova, Marketa (Journal of gastrointestinal and liver diseases, 2011)
BACKGROUND AND AIMS: Nestin is considered to be a marker of stem/progenitor cells in different tissues. Nestin expression was also described in various tumors. In pancreatic ductal adenocarcinoma (PDAC), its role in cancer cell migration, invasion, and metastases has been suggested. The study aimed at examining the expression of nestin in PDAC, and to evaluate its clinicopathological correlations. METHODS: The expression of nestin was immunohistochemically examined in 117 PDAC resection specimens, analyzed, and correlated with clinico-pathological parameters including perineural invasion (PNI). Analysis of nestin expression in nerve fibers in tissues of chronic pancreatitis (CP) was added. RESULTS: Immunohistochemical analysis of nestin expression showed 79 nestin negative (67.5 %) and 38 nestin positive (32.5 %) PDACs. No significant correlations of nestin expression in tumor cells with the analyzed clinicopathological parameters were demonstrated. Tumor grade (p<0.001) and nodal status (p=0.009) proved to represent independent prognostic factors. PNI was identified in 94 PDAC (80.3 %), and did not correlate with nestin expression. Nestin immunostaining was displayed in nerve fibers of both CP and PDAC tissues. CONCLUSION: An intimate link of nestin to a biological process of pancreatic cancer was confirmed. The expression of nestin did not prove to be a valuable prognostic factor and an immunohistochemical assessment of nestin expression is not superior to conventional prognostic factors in PDAC. A correlation between nestin expression in tumor cells and PNI was not confirmed and expression of nestin in nerve fibers of both PDAC and CP tissues seems to reflect the process of neural remodeling responsible for pancreatic neuropathy.
Keywords: duktální karcinom slinivky břišní; Chi-Square Distribution; Male; Nerve Tissue Proteins; Neoplasm Grading; prognóza; Česká republika; Kaplan-Meier Estimate; Nestin; rozdělení chí kvadrát; proteiny nervové tkáně; Carcinoma, Pancreatic Ductal; Neoplasm Invasiveness; Kaplanův-Meierův odhad; Aged; imunohistochemie; mužské pohlaví; senioři; pankreatektomie; nervová vlákna; Nerve Fibers; Pancreatic Neoplasms; Czech Republic; Lymphatic Metastasis; lidé; ženské pohlaví; Immunohistochemistry; Biomarkers, Tumor; Intermediate Filament Proteins; stupeň nádoru; Humans; invazivní růst nádoru; nádory slinivky břišní; Pancreatectomy; proteiny intermediálních filament; prediktivní hodnota testů; Prognosis; lymfatické metastázy; Female; lidé středního věku; Predictive Value of Tests; nádorové biomarkery; nestin; Middle Aged